Pengembangan media edukasi gizi berbasis android dan website serta pengaruhnya terhadap perilaku tentang gizi seimbang siswa sekolah dasar - Perdana, Fachruddin; Madanijah, Siti; Ekayanti, Ikeu (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The objective of this study were to analyze the effect of nutrition education media based on android and website to behavior and their relationships with balanced nutrition in primary school students. The design of this study was quasy experimental. A pre-post intervention study was conducted in Tuban City, East Java-Indonesia and involved 144 grades 5 primary school students. The intervention was conducted at the school by applying nutrition education media such as poster, powerpoint presentation, android, and website. A self-administered measurement with a validated questionnaire was applied to assess balanced nutrition behavior before and after the program. The result showed that a total of 72.9% school children had good knowledge, 78.5% positive attitude, 54.9% good practices on balanced nutrition before intervention. After the education program, the good knowledge, the positive attitude, and the good practices on balanced nutrition increased by 11.8%, 5.5%, and 15.9%, respectively. The media of nutrition education based on android was better than the others. In conclusion, the balanced nutrition behavior could be improved by the nutrition education program.